Trust that Mediates the Effect of Website Quality and the Electronic Word of Mouth (E-WOM) On the Purchase Intention - Sinulingga, Natalis; Handoko, Yunus; Dura, Justita (Universitas Mercu Buana, 2024)
E-commerce platforms such as Tokopedia, one of Indonesia's leading players, have attracted public attention before, during and after COVID-19 by providing various online products and services. Tokopedia is a forum or facilitator for buying and selling transactions for goods or services between sellers and buyers via the Internet. Tokopedia has become one of the e-commerce sites that can attract consumers' purchasing intentions.Objectives: This research aims to determine how trust mediates the effect of website quality and electronic word of mouth (E-WOM) on purchase intention.Methodology: This study uses a quantitative method. The analysis method used a structural equation modeling (SEM) which is processed by using SmartPLS.Finding: The research results show that electronic word of mouth (E-WOM) and trust positively and significantly affect purchase intention. Meanwhile, the website quality variable has no direct effect on purchase intentions. In addition, trust is a mediator variable for the influence of web quality and electronic word of mouth (E-WOM) on purchase intention.Conclusion: Trust is a mediator variable for the influence of web quality and electronic word of mouth (E-WOM) on purchase intention.